Pattern of Drug Abuse among Street Children of Dhaka: Inhalants are the Most Popular Drug - Masud, Jakir Hossain Bhuiyan; Khan, Md Moniruzzaman; Jesmin, - (Delta Medical College Journal, 2018)
Background: Number of street children has been rising in Dhaka, the capital of Bangladesh, in recent years and also the prevalence of substance abuse is increasing among these children. Objective: This research work focuses on understanding street children’s perception/attitudes towards substance abuse. Materials and method: For this study, an inquiry based, self-administrated questionnaire was generated and a survey was conducted by authorized, trained persons. A total of 80 participants were enrolled in this initial research work. Results: Studying respondents from two major areas of Dhaka, it came out that sniffing dendrite is the most popular adhesive/inhalant among children because of its easy availability. For these children, the initiation process of sniffing adhesives starts as a part of street culture introduced by peers (87.5%, n = 70), for getting accepted into social street gangs. Thus, these children started drug abuse as a mean of endurance along with a little pleasure/escapism, even for a while to survive within the harsh reality of street life. Data from this initial study were used to build a topological-model of present/oncoming consequences/threats of substance abuse with suggested routes of social/medical interventions. The most encouraging fact is that understanding the adverse consequences of drug abuse, most of these children wanted to quit drug abuse (70%, n = 56) and wished for a better life. Conclusion: It is believed that this model would help in implementing measures for systematic drug abuse cessation for long-term rehabilitation programmes for these children, ensuring every child’s right to have a secured, healthy life. Delta Med Col J. Jan 2018 6(1): 29-34